Electromagnetic terrorism: new hazards - Gurevich, V. (Електротехніка і електромеханіка, 2005)
A new kind of terrorism is considered, namely, electromagnetic terrorism. The history of development of this kind of weapon is described, and information on countries, companies, and leading experts in the area is given. It is shown that modern power objects are quite vulnerable to intentional electromagnetic action because of wide application of microprocessor-based protective relays and computers. Accessibility of special equipment allows carrying out successful terrorist attacks on such objects.